(untitled) (Quaderni di Gargnano, 2022)
In different sections of several works, Dante narrates how he fell in love with the so-called "donna pietosa e gentile" (noble and compassionate woman). This article offers a reading of the episode in relation to two possible sources from Andreas Cappellanus’ De amore. By comparing the Dantean passages with the conventional late-medieval rules for love, the article aims to provide a new evaluation of the changing moral emphasis that Dante brings to formulating judgement on his love for the "donna gentile", across these different works. L’articolo propone una lettura di alcuni luoghi delle opere dantesche inerenti l’episodio dell’innamoramento per la cosiddetta "donna pietosa e gentile" alla luce di due possibili ipotesti derivanti dal De amore di Andrea Cappellano. L’intento è quello di dimostrare come il confronto di questi brani danteschi con l’etica erotica tardomedievale permetta di meglio definire il giudizio morale di volta in volta formulato da Dante su quest’innamoramento.